دور شبکات التواصل الاجتماعى (الفیس بوک) فى الوعى المعلوماتى بادارة الأزمات والکوارث : دراسة استکشافیة تحلیلیة - د. نها محمد عثمان Mohamed Othman (المجلة الدولية لعلوم المكتبات والمعلومات)
The concept of crisis or catastrophe is one of the most widely heldconcepts in contemporary society, where it touches one way or another allaspects of life, from crises and disasters facing the individual, governments andinstitutions, to crises and international disasters.The world of crises and disasters is a living and interactive world, a worldwith its phases, its characteristics and its causes. The state is affected by all itsinstitutions and institutions, material, moral and human.Therefore, in our contemporary society there is an increasing importancein managing crises and disasters. It works to preserve the assets and assets ofthe Organization, its ability to generate revenues, maintain individuals andemployees against various risks, and avoid potential risks or mitigate their impacton the Organization. This is also true of the State and its administrations, as wellas the process of systematic and systematic preparation and assessment ofinternal and external problems that seriously threaten the reputation and survivalof the Organization.As a result of the importance of crisis and disaster management, eachperson must know the answer to two main questions:1- How do we manage the crises and disasters that confront us directly indifferent aspects of our lives: in our company, our organization, ouruniversities, our region, our home?